1993
DOI: 10.1007/bf01050259
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of vincristine on the peripheral nervous system

Abstract: Forty patients with Non-Hodgkin's Lymphoma treated with vincristine between 1984 and 1990 (cumulative dose 12 mg in 18-24 weeks) were investigated in order to evaluate the long term effects of vincristine on the peripheral nervous system. The patients were interviewed with emphasis on neuropathic symptoms. Physical and quantitative sensory examination with determination of vibratory perception and thermal discrimination thresholds were performed, four to 77 months (median 34 months) after vincristine treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 21 publications
3
79
0
4
Order By: Relevance
“…In their studies on motor performance in children with ALL, ReindersMesselink et al (1996ReindersMesselink et al ( , 1999ReindersMesselink et al ( , 2001 found that problems with balance and gross motor performance occurred mainly during treatment and improved with time, while fine motor problems appeared after treatment. As vincristine neuropathy is acute and decreases with time (Postma et al, 1993), it is postulated that these fine motor problems may be due to methotrexate neurotoxicity, which can have a late onset and run a chronic course (Vezmar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In their studies on motor performance in children with ALL, ReindersMesselink et al (1996ReindersMesselink et al ( , 1999ReindersMesselink et al ( , 2001 found that problems with balance and gross motor performance occurred mainly during treatment and improved with time, while fine motor problems appeared after treatment. As vincristine neuropathy is acute and decreases with time (Postma et al, 1993), it is postulated that these fine motor problems may be due to methotrexate neurotoxicity, which can have a late onset and run a chronic course (Vezmar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This toxicity is very important and is considered a major dose-limiting side effect. An autonomic neuropathy and demyelination are sometimes manifested (Postma et al, 1993). The dose level and the cumulative dose are the most important factors associated with the development of severe vincristine-induced CIPN.…”
Section: Antitubulins: Vinca Alkaloidsmentioning
confidence: 99%
“…Vincristine commonly produces isolated sensory CIPN but may be associated with severe motor neuropathy (Postma et al, 1993). This toxicity is very important and is considered a major dose-limiting side effect.…”
Section: Antitubulins: Vinca Alkaloidsmentioning
confidence: 99%
“…Painful peripheral neuropathy is one of the main side effects induced by diverse classes of chemotherapeutic agents, including vincristine (Namvaran et al, 2011b;Postma et al, 1993;Quasthoff and Hartung, 2002). Vincristine is one of the most common chemotherapeutic drugs used to treat a wide variety of malignancies, including leukemia and lymphoma, and prevents tumor cell replication through alteration of cytoskeletal structure and disorientation of microtubules (Himes et al, 1976;Owellen et al, 1976).…”
Section: Introductionmentioning
confidence: 99%